Estimation Free Cyanide on the Sites Exposed of Organisms Mortality in Sura River /November 2018 - Reyam Naji Ajmi (Journal of Global Pharma Technology, 2016)
Inductively coupled plasma mass spectrometry   (ICP-MS) and high-performance liquid chromatography hyphenated were used cyanide determination. Samples preparation, digestion, and extraction efficiency. Analytical methods for the determination of total acute toxicity of cyanide at temperatures from 4- 24 and dissolved oxygen 6.1±0.4 mg/L on different stages of five basic sites of Euphrates rivers water were more sensitive at lower temperatures. Results have been obtained from analysis of water samples with recoveries of 88.1% to 100 % and Relative Standard Deviations (RSD) of <0.05 %. This study proves the potential application of the newly developed method for the analysis of free cyanide in river waters while the study time we could not get any kind of fish especially after the mortality in November 2018.Keywords:  Hydrogen Cyanide, Euphrates, River water.